The failure to express a protein disulphide isomerase-like protein results in a floury endosperm and an endoplasmic reticulum stress response in rice - Han, Xiaohua (Oxford University Press, 2012)
The rice somaclonal mutant T3612 produces small grains with a floury endosperm, caused by the loose packing of starch granules. The positional cloning of the mutation revealed a deletion in a gene encoding a protein disulphide isomerase-like enzyme (PDIL1-1). In the wild type, PDIL1-1 was expressed throughout the plant, but most intensely in the developing grain. In T3612, its expression was abolished, resulting in a decrease in the activity of plastidial phosphorylase and pullulanase, and an increase in that of soluble starch synthase I and ADP-glucose pyrophosphorylase. The amylopectin in the T3612 endosperm showed an increase in chains with a degree of polymerization 8–13 compared with the wild type. The expression in the mutant's endosperm of certain endoplasmic reticulum stress-responsive genes was noticeably elevated. PDIL1-1 appears to play an important role in starch synthesis. Its absence is associated with endoplasmic reticulum stress in the endosperm, which is likely to underlie the formation of the floury endosperm in the T3612 mutant.